SUSTAINABILITY INSIGHTS FROM LOCAL WISDOM: THE CASE OF LUBUK LARANGAN IN PRESERVING AQUATIC BIODIVERSITY - Gunawan, Hendra (Pusat Kajian Demografi, Etnografi dan Transformasi Sosial, 2024)
This study explores the role of the traditional practice known as Lubuk Larangan in Jambi, Indonesia, as a community-based strategy for sustaining aquatic biodiversity. The research aims to understand how this local wisdom contributes to ecological conservation while supporting social and economic sustainability. A qualitative methodology was employed, involving in-depth interviews with local community leaders, participant observation, and document analysis of local regulations and customary laws. The findings reveal that Lubuk Larangan serves as a powerful conservation tool by establishing designated areas in rivers where fishing is prohibited for a specific period. This practice not only promotes the recovery of fish populations but also fosters collective community engagement in managing natural resources. The periodic lifting of restrictions allows for communal fishing events, ensuring equitable resource distribution and strengthening social cohesion. Furthermore, the study highlights the alignment of Lubuk Larangan with global sustainability goals, particularly in achieving targets related to biodiversity conservation and sustainable resource management. This research underscores the importance of integrating traditional ecological knowledge into modern sustainability frameworks, emphasizing that local wisdom can provide innovative solutions to global environmental challenges.